Is insolvency gendered? An analysis of personal debtors’ profiles in Portugal, 2011-2020 - Santos, S.; Vicente, M.; Gouveia, M. F.; Pinto-Ferreira, J. P. (Revista Jurídica Portucalense, 2025)
Household indebtedness is a phenomenon that cuts across capitalist economies. Women and men face different challenges. The cross-cutting nature of this event can be best understood by an in-depth analysis of social and economic factors contributing to a greater predisposition to situations of imminent insolvency. By developing a statistical analysis of a sample of 641 court decisions in insolvency proceedings from 2011 to 2020 in Portugal, this article aims to explore how women and men are affected by the elaboration of different debt profiles. Our data suggests that women are particularly vulnerable to economic difficulty. Gender inequality in working practices and salaries, unemployment, divorce, health conditions, and the sexual division of domestic and childcare work are phenomena that condition women's ability to pay their debts, making them more exposed to the possibility of defaulting on their loans. The study concludes that gender is an explanatory factor in personal insolvency.